The Causal Role of Mitochondrial Dynamics in Regulating Innate Immunity in Diabetes - Chang, Yen-Hsiang; Lin, Hung-Yu; Shen, Feng-Chih; Su, Yu-Jih; Chuang, Jiin-Haur; Lin, Tsu-Kung; Liou, Chia-Wei; Lin, Ching-Yi; Weng, Shao-Wen; Wang, Pei-Wen (Frontiers in Endocrinology, 2020)
Background: Plenty of evidence suggested that chronic low-grade inflammation triggered by innate immunity activation contributes to the pathogenesis of type 2 diabetes (T2D). Using the trans-mitochondrial cybrid cell model, we have demonstrated that mitochondria independently take part in the pathological process of insulin resistance (IR) and pro-inflammatory phenotype in cybrid cells harboring mitochondrial haplogroup B4, which are more likely to develop T2D. The mitochondrial network is more fragmented, and the expression of fusion-related proteins is low in Cybrid B4. We also discovered the causal role of mitochondrial dynamics (mtDYN) proteins in regulating IR in this cybrid model, and the bidirectional interaction between mtDYN and mitochondrial oxidative stress is considered etiologically important. In this study, we further investigated whether mtDYN bridges the gap between nutrient excess and chronic inflammation in T2D. Methods: Trans-mitochondrial cybrid cells derived from the 143B human osteosarcoma cell line were cultured in a medium containing glucose (25 mM) with or without saturated fatty acid (0.25 mM BSA-conjugated palmitate), and the expression of innate immunity/inflammasome molecules was compared between cybrid B4 (the major T2D-susceptible haplogroup among the Chinese population) and cybrid D4 (the major T2D-resistant haplogroup among the Chinese population). We investigated the causal relationship between mtDYN and nutrient excess-induced inflammation in cybrid B4 by genetic manipulation of mtDYN and by pharmacologically inhibiting mitochondrial fission using the Drp1 inhibitor, mdivi-1, and metformin. Results: Under nutrient excess with high fatty acid, cybrid B4 presented increased mitochondrial pro-fission profiles and enhanced chronic inflammation markers (RIG-I, MDA5, MAVS) and inflammasome (NLRP3, Caspase-1, IL-1β), whereas the levels in cybrid D4 were not or less significantly altered. In cybrid B4 under nutrient excess, overexpression of fusion proteins (Mfn1 or Mfn2) significantly repressed the expression of innate immunity/inflammasome-related molecules, while knockdown had a less significant effect. On the contrary, knockdown of fission proteins (Drp1 or Fis1) significantly repressed the expression of innate immunity/inflammasome-related molecules, while overexpression had a less significant effect. In addition, Drp1 inhibitor mdivi-1 and metformin inhibited mitochondrial fission and attenuated the pro-inflammation expression as well. Conclusion: Our results discovered the causal relationship between mtDYN and nutrient excess-induced chronic inflammation in a diabetes-susceptible cell model. Targeting mtDYN by direct interfering pro-fission can be a therapeutic intervention for chronic inflammation in T2D.